BETWEEN TRADITIONS AND TECHNOLOGY: POLITICAL RADICALISM AND THE SPECTACLE OF MASCULINITY IN CONTEMPORARY POLAND - ŚMIEJA, WOJCIECH (Society Register, 2021)
Radical movements of the Polish far-right consist, as elsewhere, mainly of young men. The strict gender binarism, the exaltation of men’s power, homosociality, brotherhood, physical strength and subordination of women are omnipresent among 'angry white men' everywhere, Poland included. However, these general characteristics have always its local variants, trajectories, and particularities. This article is an attempt to explain the phenomenon of Polish radical right movements in its local context: cultural, social, economic. The article focuses on ‘The March of Independence’ – a cyclical celebration for radical groups, which proliferates the discourses of far-right radical masculinity. In the first part, the author focuses on the social and economic background, worldview and ‘masculinist’ ideology of Polish' angry white men’ (Kimmel 2013). The second part focuses on the historical and cultural coding of their 'aggrieved entitlement' (Kimmel 2013). The third part of the essay draws on Steve's Garlick (Garlick 2016: 163−193) concept of ‘spectacular masculinity’. It analyzes how modern technology contributes to the construction of ‘spectacular’ masculinity among the participants of the march/members of radical groups.